2004
DOI: 10.1144/0016-764903-160
|View full text |Cite
|
Sign up to set email alerts
|

Dating fault reactivation by Ar/Ar laserprobe: an alternative view of apparently cogenetic mylonite–pseudotachylite assemblages

Abstract: Apparently cogenetic mylonite–pseudotachylite assemblages are commonly reported in major fault zones. They represent two very incompatible modes of deformation, and complex formation mechanisms have been proposed to explain this paradox. We report here one such assemblage from Central Norway in which apparently synchronous mylonite and pseudotachylite formation is separated by 100 Ma-mean muscovite Ar/Ar laserprobe spot ages from mylonite, and pseudotachylite matrix, are 406 ± 11 Ma and 290 ± 10 Ma respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Sinistral shearing along the Møre-Trøndelag Fault Complex could have been roughly contemporaneous with denudation of the Central Norway basement window in the footwall of the HDZ, as suggested by Séranne (1992), and probably of Early to Mid-Devonian age. Supporting this model is an 40 Ar/ 39 Ar white mica age of 406 AE 11 Ma reported from the mylonites of the Møre-Trøndelag Fault Complex by Sherlock et al (2004).…”
Section: Brittle Extension Contraction and The Role Of The Møre-trønmentioning
confidence: 80%
See 2 more Smart Citations
“…Sinistral shearing along the Møre-Trøndelag Fault Complex could have been roughly contemporaneous with denudation of the Central Norway basement window in the footwall of the HDZ, as suggested by Séranne (1992), and probably of Early to Mid-Devonian age. Supporting this model is an 40 Ar/ 39 Ar white mica age of 406 AE 11 Ma reported from the mylonites of the Møre-Trøndelag Fault Complex by Sherlock et al (2004).…”
Section: Brittle Extension Contraction and The Role Of The Møre-trønmentioning
confidence: 80%
“…Epidote-mineralized oblique, normal and strikeslip faults demonstrably cut deformation products associated with the Høybakken detachment fault, such as the pink cataclasite developed from the Eidsfjellet granite that yielded the c. 320 Ma K-feldspar age reported by Kendrick et al (2004). This deformation may be related to the Late Carboniferous-Early Permian movements along the Hitra-Snåsa Fault recorded by Watts (2001) and Sherlock et al (2004). 2004) along the Hitra-Snåsa Fault. Thus it appears that a principal trend of shortening remained at right angles to the Møre-Trøndelag Fault Complex from the Early Devonian and at least into Mid-and Late Devonian time.…”
Section: Brittle Extension Contraction and The Role Of The Møre-trønmentioning
confidence: 86%
See 1 more Smart Citation
“…Main phases of activity include early Devonian sinistral strike-slip, early Permian sinistral transtension, late Jurassic normal to dextral strike-slip faulting (Grønlie and Roberts, 1989;Séranne, 1992;Sherlock et al, 2004) and, presumably, Cenozoic normal dip-slip (Redfield et al, 2005b). These phases reflect the collapse of the Caledonian mountain chain, widespread Permian rifting, late Jurassic rifting of the northern North Sea and the mid Norway margin (Gabrielsen et al, 1999) and Cenozoic uplift of the Norwegian mountains while offshore basins were subsiding (Faleide et al, 2002;Redfield et al, 2005b).…”
Section: Geological Settingmentioning
confidence: 99%
“…To date, only a few studies have constrained the time interval between fault formation and reactivation using geochronological methods. For instance, Ar-Ar muscovite dating on mylonites and pseudotachylites from the Møre-Trøndelag Fault, Norway, has revealed that brittle deformation post-dated mylonitization by c. 100 Ma (Sherlock et al 2004).…”
Section: Introductionmentioning
confidence: 99%